2014
DOI: 10.1155/2014/412158
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation and Fibrosis in the Orbital Fat/Connective Tissue of Patients with Graves’ Orbitopathy: Clinical Implications

Abstract: Purpose. To assess FGF-β, TGF-β, and COX2 expression and immunocompetent cells in the orbital tissue of patients with severe and mild Graves' orbitopathy. Patients and Methods. Orbital tissue was taken from 27 patients with GO: (1) severe GO (n = 18), the mean clinical activity score (CAS) being 8.5 (SD 2.5); and (2) mild GO (n = 9), the mean CAS being 2.2 (SD 0.8), and from 10 individuals undergoing blepharoplasty. The expression of CD4+, CD8+, CD20+, and CD68 and FGF-β, TGF-β, and COX2 in the orbital tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 29 publications
0
35
0
4
Order By: Relevance
“…TGF-β is known to transcriptionally regulate cell growth, motility, matrix remodeling, and pericellular proteolytic activity (Samarakoon et al 2013); TGF-β is also known to stimulate PAI-1 transcription and to up-regulate the expressions of certain genes that encode elements of the ECM, such as fibronectin, collagen I, and proteoglycans in non-orbital tissues (Matrisian & Hogan 1990, Wight & Potter-Perigo 2011. Furthermore, TGF-β has been shown to be present in the orbits of GO patients (Pawlowski et al 2014). Indeed, we found that TGF-β was a potent stimulator of PAI-1 synthesis at all densities in OFs, resulting in up to a fivefold PAI-1 increase above baseline at high cell densities (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β is known to transcriptionally regulate cell growth, motility, matrix remodeling, and pericellular proteolytic activity (Samarakoon et al 2013); TGF-β is also known to stimulate PAI-1 transcription and to up-regulate the expressions of certain genes that encode elements of the ECM, such as fibronectin, collagen I, and proteoglycans in non-orbital tissues (Matrisian & Hogan 1990, Wight & Potter-Perigo 2011. Furthermore, TGF-β has been shown to be present in the orbits of GO patients (Pawlowski et al 2014). Indeed, we found that TGF-β was a potent stimulator of PAI-1 synthesis at all densities in OFs, resulting in up to a fivefold PAI-1 increase above baseline at high cell densities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PAI-1 is regulated by various cytokines and growth factors including transforming growth factor β (TGF-β) (Ghosh & Vaughan 2012). Strong TGF-β expression has been found in the orbital tissue of patients with mild and severe GO, which correlated positively with the clinical activity score (CAS) (Pawlowski et al 2014). It has been demonstrated that OFs synthesize PAI-1, and that PAI-1 expression is up-regulated by TGF-β, interferon-γ (IFN-γ), and leukoregulin (Smith et al 1992, Cao et al 1995; however, the role of PAI-1 in the pathogenesis of GO is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Значительное повышение уровня IL-17 приводит к развитию фиброза мягких ретробульбарных тканей у пациентов с ЭОП, ввиду того, что данный цитокин напрямую усиливает экспрессию αгладкомышечного актина (α-SMA) и продукцию компонентов межклеточного матрикса [52]. Также IL-17 через усиление продукции ТGF-β, индуцируется фиброгенез мягких ретробульбарных тканей вследствие стимулирования дифференцировки орбитальных фибробластов CD90+ в миофибробласты и избыточной секреции компонентов межклеточного матрикса [50,54]. Более того, IL-17 усиливает восприимчивость CD90+ к действию ТGF-β [55].…”
Section: межклеточное взаимодействие между T-хелперами 17 типа и Thy1unclassified
“…Copyright: © 2016 Houldsworth, et al 31]. In addition, angiogenesis could also play a role in the pathogenesis of GO [32,33].…”
Section: Catalase Polymorphism May Influence the Pathogenesis Of Diabmentioning
confidence: 99%